2006
DOI: 10.1191/0269215506cr925oa
|View full text |Cite
|
Sign up to set email alerts
|

Effects of visual and auditory cues on gait initiation in people with Parkinson's disease

Abstract: Transverse line visual cues enable people with Parkinson's disease to begin walking with longer steps, greater push-off force and higher velocity. Auditory cues that others have shown to improve aspects of gait in people with Parkinson's disease do not appear to have any systematic effect on the first two steps of gait initiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
112
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(117 citation statements)
references
References 22 publications
3
112
1
1
Order By: Relevance
“…He suggested that the placement of visual cues perpendicular to the direction of gait spaced one step length apart were most effective in improving gait in patients with PD. Many single-session studies have confirmed the benefit of visual cues (high-contrast transverse floor lines) [21][22][23][24]. However these open-loop feedback systems may not have long-term effects [25] unless a dedicated physical training program is established, as demonstrated in a patient trained to walk on floor cues reaching 120 percent of the uncued stride length over a 1-month period [26].…”
Section: Discussionmentioning
confidence: 99%
“…He suggested that the placement of visual cues perpendicular to the direction of gait spaced one step length apart were most effective in improving gait in patients with PD. Many single-session studies have confirmed the benefit of visual cues (high-contrast transverse floor lines) [21][22][23][24]. However these open-loop feedback systems may not have long-term effects [25] unless a dedicated physical training program is established, as demonstrated in a patient trained to walk on floor cues reaching 120 percent of the uncued stride length over a 1-month period [26].…”
Section: Discussionmentioning
confidence: 99%
“…10,12,15 Wagenaar and Beek 17 report the successful application of the perception-action coupling by means of using external information (for example, visual, auditive or tactile) in patients with gait disorders. Researchers suggest that disorders of the physiological system are the consequences of not only the structural abnormality but also the abnormality of spatiotemporal organization.…”
Section: Discussionmentioning
confidence: 99%
“…Details of each tested condition are as follows: K The visual cue condition Subjects walked at their fastest speed and stepped each pace in accordance with colored tapes that were attached on the floor at an interval equal to 40% of the subject's height (Figure 1a). 10,11 Distance between the tapes provided an External cues on gait performance in iSCI subjects S Amatachaya et al appropriate spatial adjustment (step length) for subjects to perceive by visual perception as the so-called 'visual cue.' K The auditory cue condition Subjects walked at their fastest speed and stepped each foot according to the rhythm of the metronome that was set 25% faster than the baseline cadence of the subject (Figure 1b).…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have characterized gait kinetics and kinematics in patients with PD (Morris, Iansek, Matyas, and Summers, 1998) demonstrating a degree of normal ization with the addition of transverse lines (Morris et al, 1999). Similarly, in a study of gait initiation in PD, gait velocity, push-off force and magnitude of first and second step length were significantly greater when transverse line visual cues were implemented (Jiang and Norman, 2006).…”
Section: Introductionmentioning
confidence: 99%